The value of flexible load in power systems with high renewable energy penetration. (1st December 2019) - Hungerford, Zoe; Bruce, Anna; MacGill, Iain
Abstract: Demand Side Management (DSM 1 ) and in particular load shifting has considerable potential for facilitating renewables integration. At present, dispatchable loads in power systems are often operated to run late at night when electricity demand is lowest. However, they might also be managed to facilitate increasing levels of variable renewable generation. A key challenge in estimating this potential, however, is a lack of data showing how dispatchable loads behave at an aggregated level in large systems. This paper helps to fill this gap using a case study of residential hot water systems in the Australian National Electricity Market (NEM). Drawing on detailed interval meter data from the Smart Grid Smart City trial, the potential benefit of optimized control of these systems for possible future high renewable penetrations in the NEM is quantified. Optimized dispatch within the PLEXOS® for Power Systems software environment demonstrates the potential to decrease power system operating costs as well as reducing conventional generator cycling requirements, reducing peak demand and improving renewables utilization in high renewables scenarios. Highlights: A novel method for representing flexible load in power systems models is presented. The value of flexible hot water load is assessed in high renewables scenarios in the Australian National Electricity Market. Optimized control of flexible load is particularly valuable for a renewable energy scenario with a large share of solar PV.